İstanbul Bâb Mahkemesi 304 No’lu Şer’iyye Sicilinin transkripsiyonu ve değerlendirilmesi (H.1204-1205 / M. 1790-1791) - Uğur, Dudu Merve (My University, 2019)
Osmanlı İmparatorluğu’nun hukuk tarihini belgelemesinin yanı sıra İmparatorluk tarihini her yönüyle aydınlatan şer‘iyye sicilleri, oldukça mühim bir kaynak grubunu oluşturmaktadır. Bu tez çalışmasında H. 1204-1205 / M. 1790-1791 yıllarına ait İstanbul Bab Mahkemesi 304 Numaralı Şer‘iyye Sicil Defteri incelenmiştir.

Sharia records form a precious group of source in that they both document the history of law in the Ottoman Empire and unravel the Imperial history in all aspects. This thesis analyses the Istanbul Bab Court Sharia Record Book no. 304 of the years 1204-1205 Hijri/ 1790-1791 C.E. There are 296 provisions in this book consisting of 70 leaf.
Keywords: Bilgi yönetimi; Knowledge management; şer‘iyye sicili sharia records